A role for the Ankyrin repeat containing protein Ankrd17 in Nod1‐ and Nod2‐mediated inflammatory responses. Issue 14 (24th May 2013) - Menning, Maureen; Kufer, Thomas A.
Abstract : Innate immune responses induced by the pattern‐recognition receptors Nod1 and Nod2 play pivotal roles to combat infection and to instruct adaptive immunity. Here we identify Ankrd17 as a novel binding partner of Nod2 and show that its N‐terminal domain mediates Nod2 binding. Knock‐down and overexpression analysis revealed that Ankrd17 is functionally involved in Nod2‐ and Nod1‐mediated responses in human myeloid and epithelial cells. In HeLa cells Ankrd17 contributed to pro‐inflammatory responses induced by Shigella flexneri, however not to type I interferon responses induced by Sendai virus. In conclusion, this reveals a novel function for Ankrd17 in anti‐bacterial innate immune pathways. Abstract : Ankrd17 binds human Nod2. Nod1‐ and Nod2‐mediated NF‐kappa B activation depends on Ankrd17. Ankrd17 contributes to bacterial induced innate immune responses in HeLa cells.